Analisis Strategi Diversifikasi Porduk di Pegadaian Purwokerto Mengunakan Metode General Electric - Alfarisi, Akmal Aziz; Shafrani, Yoiz Shofwa; Putri, Dewi Ayu Maharani; Dewi, Nurul Fazriyanti Aulia (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the product diversification strategy implemented by Pegadaian Purwokerto Branch and its impact on the company's financial stability. A qualitative descriptive approach was applied using a case study method through structured interviews, direct observations, and internal document analysis. The research also integrates the General Electric (GE) Matrix to map the business strength and market attractiveness of each diversified product. The findings reveal that Pegadaian’s diversified products—such as gold savings, vehicle financing, and Hajj/Umrah financing—have significantly contributed to expanding market reach and increasing revenue. This success is supported by comprehensive feasibility studies, structured risk management systems, and the operational role of branch-level human resources. Nevertheless, challenges remain, particularly in service digitalization and HR readiness. This research contributes both theoretically and practically to product development strategies in financial services, especially for state-owned enterprises seeking sustainable business growth through data-driven diversification.